The Special Reimbursement Action of Law 16.744 on Workplace Accidents and Occupational Illnesses, a View from the Perspective of Civil Law, in Attention to a Chilean Cassation Judgment - Inostroza-Adasme, S (UNIV REPUBLICA, FAC DERECHO, 2021)
Social security has proven to be an effective health insurance that guarantees protection to all inhabitants of a certain nation. In Chile it is a right that is enshrined in constitutional level. Therefore, this guarantee is the support of modern legislation that must face the challenge of safeguarding the physical and mental integrity of workers in the complex scenario of an occupational accident that causes a significant change in their lives and their families. Despite the fact that, this fundamental right has a direct link with the ius publicum, we cannot deny its connection with the other branches of law. Thus, as in this comment we will review a judgment that deals with labor matters related to social security, but which is also related to issues of civil law, specifically in the matters of obligations and responsibility. However, the main aspect of this investigation is the application of letter a), article 69 of Law 16.744, which contains a very particular action that allows the reimbursement of expenses that the administrative institution has had to incur in favor of the product worker of an accident. Consequently, this action is directed against the employer or responsible third parties. This is the context of the article we present.